Development and psychometric properties of the Suicidality: Treatment Occurring in Paediatrics (STOP) Suicidality Assessment Scale (STOP-SAS) in children and adolescents. Issue 1 (December 2016) - Flamarique, I.; Santosh, P.; Zuddas, A.; Arango, C.; Purper-Ouakil, D.; Hoekstra, P.; Coghill, D.; Schulze, U.; Dittmann, R.; Buitelaar, J.; Lievesley, K.; Frongia, R.; et al.
Abstract Background To create a self-reported, internet-based questionnaire for the assessment of suicide risk in children and adolescents. Methods As part of the EU project 'Suicidality: Treatment Occurring in Paediatrics' (STOP project), we developed web-based Patient Reported Outcome Measures (PROMs) for children and adolescents and for proxy reports by parents and clinicians in order to assess suicidality. Based on a literature review, expert panels and focus groups of patients, we developed the items of the STOP Suicidality Assessment Scale (STOP-SAS) in Spanish and English, translated it into four more languages, and optimized it for web-based presentation using the HealthTrackerTM platform. Of the total 19 questions developed for the STOP-SAS, four questions that assess low-level suicidality were identified as screening questions (three of them for use with children, and all four for use with adolescents, parents and clinicians). A total of 395 adolescents, 110 children, 637 parents and 716 clinicians completed the questionnaire using the HealthTrackerTM, allowing us to evaluate the internal consistency and convergent validity of the STOP-SAS with the clinician-rated Columbia Suicide Severity Rating Scale (C-SSRS). Validity was also assessed with the receiver operating characteristic (ROC) area of the STOP-SAS with the C-SSRS. Results The STOP-SAS comprises 19 items in its adolescent, parent, and clinician versions, and 14 items in its children's version. Good internal consistency was found for adolescents (Cronbach's alpha: 0.965), children (Cronbach's alpha: 0.922), parents (Cronbach's alpha: 0.951) and clinicians (Cronbach's alpha: 0.955) versions. A strong correlation was found between the STOP-SAS and the C-SSRS for adolescents (r:0.670), parents (r:0.548), clinicians (r:0.863) and children (r:0.654). The ROC area was good for clinicians' (0.917), adolescents' (0.834) and parents' (0.756) versions but only fair (0.683) for children's version. Conclusions The STOP-SAS is a comprehensive, web-based PROM developed on the HealthTrackerTM platform, and co-designed for use by adolescents, children, parents and clinicians. It allows the evaluation of aspects of suicidality and shows good reliability and validity.